Two stage hepatectomy with simultaneous open colon resection for multimodal treatment of colorectal liver metastases (Revista Argentina de Cirugía, 2021)
Background: the best results for hepatic metastasis of colorectal cancer are offered by hepatic resection. Approximately 50% of patients with colon and rectum cancer will develop liver metastases in the course of the disease. Bi-lobular metastases, previously considered to be unresectable may be treated by two stage stage liver resection with or without neoadjuvant chemotherapy.Objective: to describe the results upon treatment of bi-lobular colorectal metastases with a two stage strategy in which a simultaneous colon resection was done at the first stage.Material and methods: three patients were treated with a two stage strategy for simultaneous hepatic metastases of colorectal cancer. Demographic, tumor, and resection data were analyzed.Results: all three patients were able to complete the treatment. No operative mortality occurred.There was no morbidity during the first step of the resection while a complication was seen during the second step.
Keywords: colorectal metastases; liver resection